THE EDUCATIVE VALUE IN THE HADITH “ṢALLŪ KAMĀ RAʾAYTUMŪNĪ UṢALLĪ”: A PEDAGOGICAL ANALYSIS OF PROPHETIC INSTRUCTION - Cut Nyak Marlina; Syabuddin; Sri Suyanta; Zuhra Intan (Jurnal Ikhtibar Nusantara, 2025)
This study aims to examine the educational values contained in the Hadith of Prophet Muhammad ﷺ ” صَلُّوا كَمَا رَأَيْتُمُونِي أُصَلِّي” (Pray as you see me praying). This hadith is not only the main guideline in the procedure of prayer, but also contains holistic and applicable principles of Islamic education. This research uses the library research method by examining various relevant literature sources. The sanad of the hadith, the quality of the narrators, and the content (matan) of the hadith were analyzed to assess its validity and educational value. The results show that the Hadith contain the value of exemplary (uswah hasanah), visual and practical learning, internalization of the meaning of worship, the importance of standardization in education, and the need for active interaction between educators and students. These values are very relevant in building an Islamic education system that touches the spiritual, intellectual, and emotional aspects of students. Therefore, this hadith is not only important in the fiqh aspect of worship, but can also be used as a basis for developing a contextual and effective approach to Islamic education in the modern era.